The use of cosolvents in heterogeneously and homogeneously catalysed methanolysis of oil - Hájek, Martin; Vávra, Aleš; Mach, Petr; Straková, Anna (Journal of environmental management, 2020)
The paper describes transesterification of oil by methanol with use of cosolvents such as ethyl acetate, tetrahydrofuran, hexane, acetone and diethyl ether at catalyst homogeneous (potassium hydroxide) and heterogeneous (mixed oxides). The cosolvents dissolve oil and methanol to form a single (homogeneous) phase, which increases the reaction rate. Therefore, the biodiesel production will be environmentally friendly because less energy is consumed, which increases sustainability. The whole binodal curve of ternary plots of oil, methanol and cosolvent was determined to find the molar ratio, in which the reaction mixture forms a single phase. The ethyl acetate and tetrahydrofuran have relatively small heterogeneous region, because of the similarity of their electric dipole moment with methanol. After transesterification, the detailed analysis of ester and also glycerol phase was carried out. For homogeneous catalyst, the highest esters content in the ester phase was achieved with tetrahydrofuran. For heterogeneous catalyst, the ester content was lower with cosolvent than without cosolvent, probably due to dilution of reaction components by cosolvent or bonding of cosolvent to the active sites of the catalyst.
Keywords: Transesterification; biopaliva; methanol; Cosolvents; Biofuels; Heterogeneous catalyst; Methyl ester; Plant Oils; estery; Esters; Homogeneous catalyst; esterifikace; katalýza; Catalysis; oleje rostlin; Ternary plot; Esterification; Methanol